Dexmedetomidine as an Adjunct in Anesthesia for Adolescent Idiopathic Scoliosis (AIS) Surgery: A Case Series - Nofiyanto, Eko; Halimi, Radian Ahmad; Fuadi, Iwan; Abdul rachman, Iwan (Jurnal Neuroanestesi Indonesia, 2025)
Scoliosis is a spinal curvature deformity 10, with Adolescent Idiopathic Scoliosis (AIS) affecting those aged 10-18 years. The global prevalence of AIS is between 1%-2%, while in Indonesia, it stands at 2,93%, with a female-to-male ratio of 4.7:1. Perioperative challenges include nerve damage, bleeding, and postoperative pain. Neuromonitoring (MEP and SSEP) helps prevent injury, while careful drug selection supports spinal protection. Three female patients scoliosis reconstructions were performed under general anesthesia. All received target- controlled infusion (TCI) propofol, dexmedetomidine, and fentanyl, with stable hemodynamics and no neurological changes post-surgery. Epidemiological data showed that AIS predominantly affects females. The study included patients with curve progression impacting activity, with no motor or sensory abnormalities observed. Anesthesia was induced with propofol TCI (4 ?g/mL) and dexmedetomidine (0.3-0.7 mcg/kg/hr), reducing propofol and opioid use. Dexmedetomidine targets ?2-adrenergic receptors, reducing sympathetic outflow, stabilizing hemodynamics, blocking pain transmission, and improving recovery by reducing blood loss and inflammation. Dexmedetomidine provides sedation, analgesia, and stable hemodynamics in scoliosis surgery, minimizing blood loss and transfusion needs. It supports neurophysiological monitoring, reduces postoperative pain, and enhances recovery.